Varijabilnost populacija zidne gušterice Podarcis muralis (Laurenti, 1768) : doktorska disertacija - De Luca, Nina (Zagreb : N. De Luca, 1996)
Sažetak: Analiza geografske varijabilnosti popšulacija zidne gušterice Podarcis muralis (Laurenti, 1768) provedena u ovom radu imala je četiri glavna cilja: (1) opisivanje morfološke varijabilnosti i fenetičkih odnosa populacije u području od Julijskih Alpi u Sloveniji do Prespanskog jezera u Makedoniji, (2) utvrđivanje subspecifičnog statusa i taksonomskog odnosa između spomenutih populacija, koje su prethodno bile svrstane u tri podvrste: Podarcis muralis muralis, P. m. maculiventris i P.m. albanica, (3) analiza taksonomskih odnosa geografskih susjednih populacija i utvrđivanje prijelaznih (intergradacijskih) zona između podvrsta, i (4) određivanje zoogeografskih i fitogenetskih odnosa između istraženih populacija i vrste u cijelini.
Skupni uzorak od 717 odraslih primjeraka (398 mužjaka i 319 ženki) podijeljen je na 10 glavnih uzoraka, na temelju geografskog porijekla životinja i analize varijance. Univarijantne i multivarijantne statističke analize provedene su na 43 vanjsko-morfološke osobine, podijeljne u tri skupa (biometrijske, merističke i uređene osobine). Normalitet distribucije i prisustvo alometrijskih efekata testirani su prethodno. Univarijantnr metode uključivale su opisnu statistiku, analizu varijance s testom raspona, Kruskal-Wallis test i Mann-Whitney U-test. Multivarijantne metode obuhvatile su koeficijent korelacije, koeficijent srednje taksonomske udaljenosti, koeficijent jednostavnog podudaranja, koeficijent značajnosti, metode grupiranja, analizu glavnih komponenata, analizu glavnih koordinata, MDS metodu, graf najkraćeg spoja i kofenetsku korelaciju.
Rezultati su potvrdili postojanje triju podvrsta zidne gušterice u istočnom dijelu areala: nominantne podvrste Podarcis muralis muralis, sjevernojadranske podvrste P.m. maculiventris i balkanske podvrste P.m. albanica. Značajne fenetičke razlike utvrđene su između podvrsta, osobito u tjelesnim dimenzijama, broju leđnih i bedrenih ljusaka, broju subdigitalnih lamela 4 prsta stražnje noge, broju bedrenih pora, i obojenosti. Populacije podvrste P.m. muralis iz Julijskih Alpi, Velebita i Hercegovine fenetički su vrlo slične. Populacija iz sjevrnog dijela otoka Cresa fenetički je udaljenija od spomenutih kopnenih populacija, ali također pripada podvrsti P.m. muralis. Analiza uzoraka iz obalnog dijela Istre, grada Rijeke, i grada Cresa, potvrdila je pripadnost ovih populacija podvrsti P.m.maculiventris.
Istražni uzorci ove podvrste međusobno su fenetički bliski i tvore zajedničku grupu u svim analizama. Otočne populacije arhipelaga u Skadrskom jezeru i populacija s otoka Golemgrada u Prespanskom jezeru grupiraju se zajedno i pripadaju podvrsti P.m.albanica. Ove dvije populacije fenetički su najviše udaljene od ostalih proučenih populacija. Golemgradska populacija također se razlikuje od ostalih populacija riđom obojenošću grla i trbuha. Navedena razlika ipak ne opravdava opisivanje golemgradske populacije kao zasebne podvrste. Populacija s Ohridskog jezera, prethodno svrstana u podvrstu P.m. albanica, zauzimala je središnji položaj između sve tri podvrste u većini analiza. Njena subspecifička pripadnost, stoga, nije mogla biti sa sigurnošću određena.
Detaljna analiza primjeraka zidne gušterice iz Rijeke i Grobničkog Polja pokazala je da riječka populacija posjeduje neke značajke hibridne populacije, prije svega pojavljivanje muralis tipa obojenosti kod pojedinih životinja i veliku morfološku varijabilnost. Ovi rezultati potvrđuju postojanje intergradacijske zone između podvrsta P.m. muralis i P.m. maculiventris u riječkom području. Nalazi životinja s hibridnim značajkama upućuju na mogućnost da je spomenuta intergradacijska zona sekundarnog karaktera. Populacije zidne gušterice s otoka Cresa jedine su otočne populacije ove vrste u Jadranu. Istraživanja su pokazala da postoji velika Fenetička udaljenost između dvije podvrste na otoku kao i prostorna i ekološka izolacija.
Jasna fenetička sličnost između populacija iz grada Cresa i kopnenih populacija P.m. maculiventris, kao i ograničen areal ove podvrste na otoku isključivo na grad Cres, ukazuje na relativno recentno, vjerojatno antropogeno, doseljavanje podvrste P.m. maculiventris na otok Cres. S druge strane, fenetička i taksonomska udaljenost populacije iz sjevernog dijela otoka od kopnenih muralis populacija uzrokovana je, po svemu sudeći, dugotrajnom izolacijom. Stoga se može zaključiti da creski P.m. muralis predstavlja glacijalni relikt, odvojen od kopnenih populacija podizanjem razine mora u ranom postglacijalu. Središnji polžaj populacije s Ohridskog jezera između podvrsta P.m. muralis i P.m. albanica potvrđen je detaljnom analizom svih primjeraka s Ohridskog, Skadarskog i Prespanskog jezera, te iz zapadne Hercegovine.
Po svemu sudeći, dio kontaktne zone između dvije podvrste prolazi istočnom obalom Ohridskog jezera. Nije moguće, međutim, odrediti da li kontaktna zona ima primarni ili sekundrani karatkter. Također, ohridska populacija pokazuje fenetičku sličnost s uzorcima podvrste P.m. maculiventris, što ukazuje na mogućnost zajedničkog porijekla dvije istočnomediteranske podvrste zidne gušterice. Zoogeografska analiza do sada poznatog areala i novootkrivenih nalazišta, zajedno s rezultatima taksonomske analize, ukazuje na mogućnost da je gaografska varijabilnost populacije zidne gušterice u istočnom dijeli areala povezana s geološkim i klimatskim promjenama u pleistocenu i postpleistocenu.
U ovm radu predložene su tri moguće hipoteze: (1) glacijacije su uzrokovale cijepanje kontinuiranih populacija zajedničkog pretka u tri mediteranska glacijalna refugija, a meditranske svojte Jadranskog bazena i Apeninskog poluotoka (P.m. nigriventris, P.m. maculiventris i P.m. albanica) porijeklom su iz istočnomediteranskog refugija, (2) mediteranske svojte sjevernojadranske obale i Apeninskog poluotoka (P.m. nigriventris i P.m. maculiventris) su zapadnomediteranskog porijekla, a P.m. albanica je istočnomediteranskog porijekla, i (3) subspecifička diferencijacija populacija zidne gušterice u području istočnog Mediterana posljedica je parapraktičke specijacije u uskoj obalnoj zoni s oštrim ekološkim gradijentom.
Iz prve dvije hipoteze proizlazi da su intergradacijske zone između podvrsta zidne gušterice u istočnom dijelu areala sekundrane, dakle hibridne zone, dok treća hipoteza pretpostavlja da intergradacijske zone imaju primarni karakter. Ukrtako, rezultati istraživanja upućuju na zajedničko porijeklo dvije mediteranske podvrste P.m. maculiventris i P.m. albanica i postojanje sekundarnih intrgradacijskih zona između svake od spomenutih podvrsta i nominantne podvrste P.m. muralis. Postojanje reliktnih populacija nominantne podvrste na Apeninskom poluotoku i na otoku Cresu dokazuje da su predačke populacije ove podvrste preživjele pleistocenske glacijale u području Jadranskog bazena.
Termofilne populacije, s druge strane, mogle su preživjeti glacijacije u refugijima južne Grčke i Male Azije i migrirati na sjever i sjeverozapad u postglacijalnom razdoblju, nakon izdizanja razine mora i odvajanja otika Cresa od kopna. Ovakvim slijedom događaja može se objasniti fenetička sličnost danas geografski izoliranih podvrsta P.m. maculiventris i P.m. albanica, kao i fenetički i zoogeografski odnosi dviju podvrsta na otoku Cresu. Odsutstvo intergradacijske zone između podvrsta na otoku u suprotnosti je s hipotezom o parapatričkoj specijaciji i upućuje na recentno, antropogeno naseljavanje podvrste P.m. maculiventris u grad Cres.
U svakom slučaju, daljnja taksonomska istraživanja, osbito u područjima utvrđenih intergradacijskih zona između podvrsta, bit će od osobite važnosti za potvrđivanje ovdje predložene teorije o filogenetskom razvoju i taksonomskim odnosima populacija zidne gušterice u području Jadranskog bazena.
Abstract: This sttudy of the geographic variations among populations of the Common Wall Lizard Podarcis muralis (Laurenti 1768) had four major objectives: (1) to describe morphological variability of populations in an area ranging from Julian Alps in Slovenia to Prespa Lake in Macedonia and determine phenetic relationship between them, (2) to determine subspecific status and interspecific taxonimical relationship among those populations, that were previously described as three different subspecies (P.m. muralis, P.m. maculiventris and P.m. albanica) or were not given any subcpecific status at all, (3) to analyze taxonomical relationship between contiguous, as well as insular populations, belonging to different subspecies, and, consequently, to determine the status and extent of the intergradation zones
(4) to determine zoogeographical relationships among Common Wall Lizard's populations in southestern part of species distribution range and set hypotheses about intraspecific phylogenetic relationships. A composite sample of 717 adult specimens (398 males and 319 females) was dividend in 10 subsamples (with males and females separated), based on their geographical origin and results of a one-way ANOVA test. Univariate and multivariate statistical methods were perormed using 43 external morphological characteristic dividend into the following theresubsets: biometric, scalation and ordered. All the variables were previously checked for normality and allometric effects. Univariante statistical methods included descriptive statistics, one-way ANOVA with multiple range test, Kruskal-Wallis test and Mann-Whitney U-test.
Multivariate methods included correlation coefficient, average taxonomic distance coefficient, simple matching coefficient, coefficient of significance, cluster analysis, principal component analysis, principal coordinate analysis, nonlinear multiidmensional scaling, minimum spanning tree and cophenetic correlation. Both univariante and multivariante methods confirmed that three different subspacies exist in eastern part of the species distribution range: nomintypic, continentally adapted P.m. muralis, and two thermophilous subspecies, P.m. maculiventris in northeastern Adriatic region, and P.m. albanica in southestern part of the investigated area.
Significant phenetic differences were found between subspecies, especially in body size, numbers of dorsal and femoral scales, numbers of subdigital lamellas and femoral pores, and body coloration and pattern. P.m. muralis samples from Julian Alps, Velebit mountains and western Herzegovina clustered closley together, while insular muralis population from the northern part of the island of Cres showed obvious phenetic distance. Still, this population should be given muralis subspecific status since it is more closly related to this than to any other subspecies. Samples from Istria Peninsula, Rijeka and town Cres on island of Cres on island of Cres belong to P.m. maculiventris. They showed close phenetic similarity and were consistently clustered together in all analyses.
Insular populations from Skadar Lake Archipelago and island Golemgrad on Prespa Lake represent P.m. albanica pair, most phenetically distinc from all other populations studied. Golemgrad population differs from other population with it's red belly coloration and absence of dark spots on throat and belly. However, this particular difference by itself does not justify ranking this population as a new subspecies. It was not posible to determine subspecific status of Ohrid Lake population with certainty, since it's sample hold the intermediante position between all other samples. Detailed study of Rijeka and Grobničko Polje specimens showed that in Rijeka population some hybrid characteristic can be foun. This includes existence of explicit muralis morphological characters in some specimens and increased morphological variability.
While Rijeka population still should be classified as P.m. maculiventris, these results established Rijeka region as part of the intergradation zone between P.m. muralis and P.m. maculiventris. Specimens with hybrid characteristics found in Rijeka population indicate that this region may reperesent a secondary intergradation zone between two subspecies. Island Cres population are the only insular Common Wall Lizard population in the Adriatic Sea. This study demonstrated the existence of the great phenetic distance between two subspecies on the island, as well as their entire spatial and ecological isolation. Close phenetic similarity between population from the town Cres and coastal maculaventris populations is an evidence of relatively recent, probably anthropogenic spreading of P.m.maculiventris on island Cres.
This is also indicated by the fact that this population is present exclusively in the town of Cres and nowhere else on the island. In contrast, population from the northern part of the island showed obvious phenetic distance compared to its continental counterparts, caused apparently by long-term spatial isolation. Consequently, this population can be easely described as glacio-relic population, that was isolated by sea-level rise in the early postglacial times and has survived in higher forested parts of the island with cooler bioclimatic conditions. Intermediante position of the Ohrid Lake population between P.m. muralis and P.m. albanica was confirmed with detailed, specimens-based study. It is likly that a segment of the intergradation zone between two subspecies is situated in the region along the eastern coast of the Ohrid Lake.
However, it is not possible at this point to speculate about the character of this intergradation zone. Importantly, Ohrid Lake population also seems to be phenetically close to geographically distinct P.m. maculiventris populations, indicatingcommon origin of the two mediterranean subspecies. Zoogeographical analyses of known distribution range and newly established localities, together with results of the txonomic study, indicate that the pattern of the geographical variability of Common Wall Lizard's populations may be related to geological and climatic events during the Pleistocene. There hypoteses were proposed as a result of this work
(1) Pleistocene glaciations dividend continuous areal into three mediterranean refugia and mediterranean subspeces P.m. nigriventris, P.m. maculiventris and P.m. albanica have common, eastern-mediterranean origin, (2) P.m. nigriventris and P.m. maculiventris have common, western-mediterranean origin, while P.m. albanica has eastern-mediterranean origin, and (3) recent subspecific status of eastern Common Wall lizard's populations is a consequence of a parapractic differentiation in a narrow coastal zone with a sharp ecological gradient. Consequently, if any of the first two hypotheses is correct, recent transition zones between mediterranean and nominotypical subspecies are result of secodary contact.
In contrast, third hypothesis indicates that transition zones reperesent primary intergradation zone, caused by a corresponding change in environmental conditions. Results of this study can be best explained by assuming the common origin of eastern-mediterranean subspecies and present existence of secondary intergaradation zones between P.m. muralis and P.m. maculiventris, and P.m. muralis and P.m. albanica, respectively. Ancestral populations of today's nominotypic subspecies could have survived glacial events in Adriatic basin region, which is proved by existence of several relict muralis populations on Apeninian Peninsula and island of Cres.
Thermophileous population were likely to survive in southern Greece and Asia Minor refugia and migrate northon and north-west in postglacial times, extending its areal toward northern Adriatic region during the substantial sea-level rise, that separated most Adriatic islands (including Cres) from the mainland. That could explain phenetic similarities between two mediterranean subspecies, as well as phenetic and spatial relationship between P.m. muralis and P.m. maculiventris on the island of Cres. Lack of the intergradation zone between two subspecies on the island contradicts the hypothesis about parapatric differentiation and support the speculation about recent, anthropogenic arrival of P.m. maculiventris on island of Cres.
However, this theory needs more support in future studies, especially in the intergradation zones, before it may be fully accepted.
Doktor prirodnih znanosti - biologija
Sveučilište u Zagrebu, Prirodoslovno-matematički fakultet, Zagreb, 1996
Bibliografija: str. 245-252
Sažetak
Keywords: Gušterice -- Geografska rasprostranjenost -- Klimatski faktori